If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -40 = 50 Reorder the terms: -40 + 6x = 50 Solving -40 + 6x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 6x = 50 + 40 Combine like terms: -40 + 40 = 0 0 + 6x = 50 + 40 6x = 50 + 40 Combine like terms: 50 + 40 = 90 6x = 90 Divide each side by '6'. x = 15 Simplifying x = 15
| 2+5m=17 | | x-1=13-6x | | X+88=x+108 | | 3y=15-6 | | 11=4y+2 | | 2r/5+7r/15= | | 3a+b=-2 | | 0.9=8.1 | | 8(1-7a)=-384 | | 2x-3(-1x+9)-27=-12 | | 5a-6m+x+2y=10 | | 4x-36=9 | | 6x-7=115 | | f(x)=27x-x^3 | | 28x-24=144 | | x-2(x+12)=90 | | -45+5x=-2x+39 | | -6x-3x=4 | | 3x+10+4x-8+11x+2y=180 | | -15=0.2h | | x+0.18x=20.06 | | 11x-24=144 | | 2x+2=-2y | | 3g=1g+20 | | kx^2+5x+3=0 | | 18n-46=44 | | -3y+10=y+30 | | 7(2x-5)-3x=42 | | -7+r=-22 | | 22.7b=-204.3 | | -4(2y+2)-10=-6(y+4)+2y | | 54=8n+22 |